Size structure, weight-length relationship and condition factor K of the endogenous Cameroon giant frog Conraua goliath (Boulenger, 1906) in its natural environment - Liliane Fleurette Moumegni Monthe; Claudine Tekounegning Tiogue; Ferdinand Ngoula; Joseph Tchoumboue (International Journal of Aquaculture Research and Development, 2023)
The growth characteristics of Conraua goliath (Boulenger, 1906), an endemic and endangered species in Cameroon, were evaluated in its natural habitat between October 2021 and November 2022 in order to contribute to its domestication and conservation. For this purpose, 139 specimens (55 males, 55 females, and 29 individuals of undifferentiated sex) were collected by fishermen from 3 sites (Loum, Penja, and Nlonako) in the Department of Moungo, Coastal Region of Cameroon. The frogs were measured, and their growth parameters were determined after dissection and macroscopic and microscopic observations. The maximum size observed is 33.5 cm (SVL) and 2529 g body weight (BW), and the minimum size is 5.3 cm (SVL) and 12 g body weight (BW). This species is more abundant in the rainy season, in frogs between 18 and 24 cm, and has a Caucasian and uni-modal size structure. Independent of sex and season, this species has a significant and high regression coefficient between length, weight, and isometric growth pattern. However, this growth varies according to sex. It ranges from isometric in males (b = 2.82) and undifferentiated sexes (b = 2.85) to negative allometry in females (b = 2.21). The condition factor K ranges from 3.28 to 14.24 (mean: 7.80 ± 1.95) and fluctuates according to the sex and size of the frog. According to our results, this species has a large size and a high growth rate and could therefore be an excellent candidate for domestication to ensure its conservation. However, studies on reproductive characteristics are needed to complete this work.
Keywords: African giant frog